GATA1 Gene Polymorphisms in Down Syndrome Patients - Ponkhoon, Kherlen; Bayarmagnai, Uranchimeg; Jav, Sarantuya; Tumurkhuu, Munkhtuya (Central Asian Journal of Medical Sciences, 2017)
Objectives: Down syndrome (DS) patients have a 500 fold higher possibility of developing acute megakaryoblastic leukemia (AMKL), compared with the general population. GATA1 mutations, acquired in the early prenatal stages, contributes to leukemogenesis in AMKL and has been the explanation for the cause of early hematopoietic disorders. The aim of this study was to investigate the influence of GATA1 gene polymorphisms in patients with DS. Methods: Thirty-nine DS patients, aged ≤ 4 years, were recruited into the study. GATA1 gene polymorphisms were identified by unidirectional deep sequencing. Results: GATA1 gene polymorphisms were identified in four patients: proband-11 had GATA1 gene polymorphism, NP_002040.1:p.His71Arg (rs374300356); proband-17 had NP_002040.1:p. Tyr69Cys; proband-19 had NP_002040.1:p.Lys100Arg; and proband-20 had NP_002040.1:p. Tyr69Cys. Analyzing these GATA1 gene polymorphisms with 14 different software programs to evaluate its pathogenicity showed that NP_002040.1:p.His71Arg had damaging effects on GATA1 gene function. Conclusion: We identified four GATA1 gene polymorphisms in this cohort of 39 patients. The polymorphism identified in proband-11 (NP_002040.1:p.His71Arg) has possible damaging effects on gene regulation, and thus, we recommend routine clinical examination in this patient.